The Metamorphosis. The impact of a young family member’s problematic substance use on family life: a meta-ethnography - Sari Kaarina Lindeman; Lennart Lorås; Kristine Berg Titlestad; Terese Bondas (International Journal of Qualitative Studies on Health & Well-Being, 2023)
Purpose This meta-ethnography seeks to provide insight into the impact that a young family member’s problematic substance use has on family life. Background Problematic substance use (PSU) usually emerges in adolescence or young adulthood. Living with a family member with PSU is highly stressful. An understanding is needed of families’ experiences and their needs for adapted help and support, hence we have explored the impact of a young family member’s PSU on family life. Methods Systematic literature searches for qualitative research that explores the impact of PSU on family life and family relationships were conducted and the seven stages of meta-ethnography were used. Results Fifteen articles were included. The Metamorphosis was established as an overarching metaphor. Five main themes accompany this metaphor: stranger in the family; injuring chaos; no trust any more; family lock-up; and helpless societies. Conclusion The Metamorphosis reflects the all-embracing change experienced by families. Family members have felt powerless and helpless; often they wish to stay involved but do not know how. PSU at a young age can develop into lifelong chronic health challenges. Family-oriented help must be readily available in this phase as parents and siblings become deeply involved. Family involvement is seldom incorporated into routine treatment practices; such incorporation is therefore needed.